A Qualitative Exploration Of Job Satisfaction Among HIV-Positive Workers At Indoraya Manufacturing Plant - Siti Latipah; Naryati Naryati; Aisyah Aisyah; Giri Widakdo; Nuraenah Nuraenah (International Journal Of Community Service, 2025)
HIV/AIDS remains a global health challenge, particularly among individuals in their productive years, including factory workers. According to UNAIDS (2024), approximately 39 million people aged 15-49 live with HIV, directly affecting the labor sector (UNAIDS, 2024). In industrial settings, workers often face vulnerabilities such as long working hours, high mobility, varied education levels, and limited access to health information-factors that increase their risk of HIV infection. This study aims to explore the job satisfaction of workers living with HIV/AIDS within the industrial sector. Using a qualitative phenomenological approach, the research was conducted with 10-15 workers at a textile factory in Tangerang, selected through purposive sampling. The study focuses on understanding the experiences and perceptions of these workers regarding job satisfaction and the influencing factors. Findings reveal that job satisfaction among workers living with HIV/AIDS is strongly influenced by social and structural factors, including social support and workplace policies. According to Maslow’s hierarchy of needs, the need for safety and social acceptance is essential before individuals can achieve self-actualization in their work. Furthermore, Erving Goffman’s stigma theory explains how being HIV-positive can become a source of social pressure, hindering active participation in the workplace unless the work environment consciously addresses stigma and discrimination. The study recommends that companies implement more inclusive and proactive workplace policies. Suggested strategies include regular HIV/AIDS education, provision of Voluntary Counseling and Testing (VCT) services, enforcement of non-discrimination policies, formation of internal support groups. Collaborative efforts among companies, co-workers, and the individuals themselves are essential to creating a safe, inclusive, and productive work environment for all, including those living with HIV/AIDS.